MODEL BIMBINGAN AGAMA ANAK JALANAN DI JALUR PANTURA - Mubasyaroh Mubasyaroh (LP2M IAIN kUDUS, 2014)
RELIGIOUS GUIDANCE MODEL OF STREET CHILDREN IN PANTURA, The phenomenon of street children in Indonesia is a complex social issue. In every year of their existence are constantly undergoing significant development. Their existence has raised a new round of social exploitation by making them human periphery. Street children is a reality that is continuous to be examined. Their existence was always present as a problem that no end of its roots. The reality was very complex so that demands careful handling, serious, focused and continuous. The result of this research shows that the model of religious guidance in the area of the former County of Pati use fusion model because it was implemented by TKSK (Sub-district Volunteers Welfare Labor) under the Social Service and integrated with educational activities and exercise, as well as by volunteering independently. The third model of the religious guidance of street children that is in Kudus, Pati and Rembang, the religious guidance model in Kudus implemented by volunteers independently that have a uniqueness and advantages. In addition to the hours of work done by following street children and carried out in the places where they make a living, the guidance which was held in Kudus took place in a relaxed atmosphere, and performed by the teens so that authors call it peer counseling. As for the impact of religious guidance against street children; increased understanding of their religion, but not so significantly affect behavior change and their religiosity.